Concordance between Sources of Morbidity Reports: Self-Reports and Medical Records - Jones, Michael P.; Bartrop, Roger; Dickson, Hugh; Forcier, Lina (Frontiers in Pharmacology, 2011)
As part of a ten year follow-up study of morbidity following spouse bereavement, concordance between subject reports of their illness experience and that given by their doctors' and other medical records has been assessed. Enumeration from medical records involved extensive and careful perusal of general practitioner, specialist and hospital records while subject reports were aided by a structured questionnaire which helped to prompt subjects' memories. The findings showed generally poor concordance between these two sources of morbidity data. Overall only 22% of disease events were found in both sources:; of the diseases that did not match 65% were from the record source and 35% were from the self-report source. Despite finding that concordance rates varied with some subject and disease factors, concordance was always less than might be expected to occur by random chance (the throw of a coin). These findings have serious implications for epidemiological and pharmacoeconomic research involving morbidity history as they suggest that neither the subject nor their medical record can generally be assumed to provide a complete enumeration of morbidity burden. Indeed, irrespective of the significant factors under consideration, the maximum concordance reached in this study was 45.7%.